COVID-19 Pandemic and the Health and Well-being of Vulnerable People in Vietnam - Hai-Anh Dang; Minh N. N. Do (Institute of Labor Economics (IZA), 2022)
Despite a sizable population and modest status as a low middle-income country, Vietnam has recorded a low COVID-19 fatality rate that rivals those of richer countries with far larger spending on health. We offer an early review of the emerging literatures in public health and economics on the pandemic effects in Vietnam, with a specific focus on vulnerable population groups. Our review suggests that vulnerable workers were at more health risks than the general population. The pandemic reduced household income, increased the poverty rate, and worsened wage equality. It increased the proportion of below-minimum wage workers by 2.5 percentage points (i.e., 32 percent increase). While government policy responses were generally regarded as effective, the public support for these responses was essential for this success, particularly where there were stronger public participation in the political process. Our review also indicates the need for a social protection database to identify the poor and the informal workers to further enhance targeting efforts. Finally, we suggest future directions for research in the Vietnamese context.
Keywords: E24; I1; I30; J21; O12; 330; COVID-19; health; vulnerable households; poverty; inequality; Vietnam